A Frustrated Lewis Pair Based on a Cationic Aluminum Complex and Triphenylphosphine - Stennett, Thomas; Pahl, Jürgen; Zijlstra, Harmen; Seidel, Falk W.; Harder, Sjoerd (Organometallics, 2016)
The highly Lewis acidic, cationic aluminum species [DIPP-nacnacAlMe](+)[B(C6F5)(4)](-) (1, DIPP-nacnac = [HCC(Me)N(2,6-(Pr2C6H3)-Pr-i)(2)](-)) has been shown to undergo reactions with a wide variety of small molecules, in both the presence and absence of an external weak phosphine base, PPh3. Cycloaddition reactions of unsaturated C C bonds across the aluminum diketiminate framework are reported, and the first structural confirmation of this type of cycloaddition product is presented. Addition of PPh3 to 1 produces the cationic aluminum phosphine complex [DIPP-nacnacAl(Me)PPh3](+)[B(C6F5)(4)](-), which undergoes fluxional dissociation/coordination of the phosphine in solution. This weak Al-P interaction can be utilized in frustrated Lewis pair type reactions to activate alkenes, alkynes, CO2, propylene oxide, and the C-Cl bonds of CH2Cl2. The CO2 adduct [DIPP-nacnacAl(Me)OC-(PPh3)O](+)[B(C6F3)(4)](-) undergoes further stoichiometric reduction with Et3SiH to produce an aluminum formate species.

Oxide-Bridged Heterobimetallic Aluminum/Zirconium Catalysts for Ethylene Polymerization - Boulho, Cedric; Zijlstra, Harmen; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2015)
A bimetallic aluminum/zirconium complex Cp*Zr-2(Me)OAl(DIPH) [DIPH-H-2 = 3,3-bis(2-methylallyl)-(1,1-biphenyl)-2,2-diol; Cp* = C5Me5] was prepared in good yield by the reaction of (DIPH)AlMe with Cp*Zr-2(Me)OH. In contrast to Roesky's catalyst, Cp2Zr(Me)O(Me)Al(DIPP-nacnac) DIPP-nacnac = CH[(CMe)(2,6-iPr(2)C(6)H(3)N)](2), it contains no Al-Me functionality and has increased Lewis acidity at Al. Crystal structures and the NMR spectra of the aluminum complex (DIPH)AlMe and the bimetallic Al/Zr species reveal in both cases dimeric complexes. The crystal structure of [Cp*Zr-2(Me)OAl(DIPH)](2) shows a planar Al2O2 core and a terminal Cp*Zr-2(Me)O group. Ethylene polymerization in toluene was studied for the bimetallic complex with a variety of scavengers. Under comparable polymerization conditions, the methylalumoxane-activated species show high activities that are similar to those obtained with Cp*2ZrCl2 and Roesky's bimetallic complex Cp2Zr(Me)OAl(Me)(DIPP-nacnac), with a relatively narrow polydispersity index (2.47).
Keywords: Sandwich complexes; Heterometallic complexes; Zirconium; Polymerization; Polyethylene